STRUKTUR VEGETASI SEKITAR JENIS POHON TANDUI (Mangifera rufocustata KOSTREM.) DI HULU SUNGAI SELATAN - Adistina Fitriani; Eva Prihatiningtyas (Lambung Mangkurat University-Indonesia, 2021)
This research aims to analyze the vegetation that grow around the tandui plants/ This research done to support for the ex situ and in situ conservation of natural resources,The data collected in this research used proposive sampling methodd with 15 observation plots starting from seedlings, saplings, poles and trees. The analysis data was used the Importance Value Index (INP). The results showed that the seedling rate was dominated by Jambu Air (Syzygium aqueum) 114.65%, Karet (Hevea brasiliensis) 63.38%, Ramania (Bouea macrophylla) 47.92%, sapling rate was dominated by Karet (Hevea brasiliensis) 60.5%, Jambu Biji (Syzygium aqueum) 48.19%, Jingah (Gluta renghas) 41.77%, the pole level was dominated by Karet (Hevea brasiliensis) 175.60%, Rambutan (Nephelium lappaceum) 148.62% , Sungkai (Peronema canescens) 126.64% and the tree level is dominated by Rubber (Hevea brasiliensis) 191.82%, Kelapa (Cocos nucifera) 108.78% and Langsat (Lansium domesticum) 84.60%